ILLEGAL LAND GRAB: ISRAEL'S SEIZURE OF LAND IN PALESTINE - Saleh Raed Shatat; Ong Argo Victoria (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
Since 1967, each Israeli government has invested significant resources in establishing and expanding the settlements in the Occupied Territories, both in terms of the area of land they occupy and in terms of population. As a result of this policy, approximately 380,000 Israeli citizens now live on the settlements on the West Bank, including those established in East Jerusalem (this report does not relate to the settlements in the Gaza Strip). During the first decade following the occupation, the Ma'arach governments operated on the basis of the Alon Plan, which advocated the establishment of settlements in areas perceived as having